Impact of Internal Factors on ICAO English Language Proficiency Test Failure at Jakarta Air Traffic Service Centre - Erga Maulida; Dwi Lestary; Elfi Amir (CV. AFDIFAL MAJU BERKAH, 2026)
English communication proficiency is a critical requirement for ensuring safety in international aviation operations. Air Traffic Controllers (ATCs) in Indonesia are required to meet the ICAO English Language Proficiency (IELP) Level 4 standard; however, the failure rate of the IELP Test at the Jakarta Air Traffic Service Centre (JATSC) remains relatively high. This study aims to analyze the influence of internal factors on IELP test failure among ATCs at JATSC. The research employed a quantitative approach using a survey method. Data were collected from 50 ATCs selected through stratified random sampling based on work experience. Internal factors examined included basic English proficiency, motivation, language anxiety, self-confidence, learning style, and linguistic performance. Data were analyzed using descriptive statistics, normality testing, correlation analysis, and simple linear regression. The results indicate that internal factors have a significant influence on IELP test failure, with language anxiety, limited motivation, and insufficient linguistic performance emerging as dominant contributors. These findings suggest that internal psychological and cognitive aspects play a crucial role in determining IELP outcomes. The study concludes that targeted interventions focusing on strengthening internal factors are essential to improve IELP test success rates and enhance aviation communication safety at JATSC.